2018
DOI: 10.15567/mljekarstvo.2018.0104
|View full text |Cite
|
Sign up to set email alerts
|

The influence of feed supplementation with linseed oil and linseed extrudate on fatty acid profile in goat yoghurt drinks

Abstract: Feed composition is one of the most influential factors affecting fatty acid profile of milk products. The aim of this study was to investigate the influence of linseed oil and linseed extrudate supplementation on fatty acid composition of goat prebiotic and probiotic yogurt drinks. Thirty six White Shorthaired dairy goats at the beginning of their third lactation period were divided into two experimental and one control group, each comprising twelve animals. Goats in the experimental groups were given either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Changes in the FA profile of goat milk and the fermented products (kefir, yoghurt, yoghurt drink) manufactured from it were also found out (CAIS-SOKOLIŃSKA et al, 2015;SUMARMONO et al, 2015;BORKOVA et al, 2018). Moreover, the study on FA composition of kefir (CAIS-SOKOLIŃSKA et al, 2015) showed that it remains relatively stable during both the manufacturing and storage for 21 days (as compared to the FA composition of raw material).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Changes in the FA profile of goat milk and the fermented products (kefir, yoghurt, yoghurt drink) manufactured from it were also found out (CAIS-SOKOLIŃSKA et al, 2015;SUMARMONO et al, 2015;BORKOVA et al, 2018). Moreover, the study on FA composition of kefir (CAIS-SOKOLIŃSKA et al, 2015) showed that it remains relatively stable during both the manufacturing and storage for 21 days (as compared to the FA composition of raw material).…”
Section: Resultsmentioning
confidence: 86%
“…- In yoghurt, both the volatile FA proportion (VFA; 15.39% (milk) vs. 14.81% (yoghurt)) and short-chain FA proportion (SCFA; 21.61% (milk) vs. 21.03% (yoghurt)) decreased. This could be explained by the fermentation activity of lactic acid bacteria (JIA et al, 2016) or due to an effect of the fermentation process because of the volatile character of VFAs and SCFAs (BORKOVÁ et al, 2015;CAIS-SOKOLIŃSKA et al, 2015). The proportion of FA groups in milk corresponded with their proportion in yoghurt.…”
Section: Parametermentioning
confidence: 96%
See 1 more Smart Citation
“…In 2013, only the goats in first lactation were included; in 2014, the animals in second lactation were selected; in the following years (2015-2017), only the animals in third lactation were included. The methodology for determining the FA content has been described by Borková et al [1]. Based on the obtained results, the atherogenic index (AI) [AI = (C12:0 + 4 × C14:0 + C16:0) / (monounsaturated fatty acid + polyunsaturated fatty acid)] was calculated.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The fat in yoghurt drinks was extracted according to the Czech national standard ČSN EN ISO 1211 (2011). Fatty acids were then re-esterified into the corresponding methyl esters (FAMEs) and analysed by gas chromatography (GC) according to the method and GC parameters described by Borková et al (2018). Thirty-seven FAMEs were identified using external analytical standards (Supelco -Merck KGaA, Darmstadt, German).…”
Section: Fatty Acid Analysismentioning
confidence: 99%